Level of Job Satisfaction among Registered Nurses Working in Clinical Area at DHQ Teaching Hospital, Dera Ghazi Khan - Malik Gorah, Rabia Noureen; Mukhtar, Madiha (Basic and Applied Nursing Research Journal, 2021)
To assess the level of job satisfaction among registered nurses working in clinical area at Teaching Hospital Dera Ghazi Khan. Method: A cross sectional descriptive survey was used to assess the level of job satisfaction among registered nurses. Random sampling technique was used to collect the data. Sample size consists of 102 registered nurses, out of 121, working in clinical area at DHQ Teaching Hospital Dera Ghazi Khan. I developed one Likert scale with consisted 30 questions to measure the Level of Job satisfaction among registered Nurses. Computer analysis was done with statistical package for social sciences (SPSS) version 18. Descriptive statistics were taken out depending on the type of variable under study. Result: Study included 102 registered nurses to assess the level of job satisfaction. Results showed that from 102 respondents, 18 (17,65% answers in strongly satisfied category,45 (44.12% answers in satisfied category, 25 (24.51%) answers in neutral category, 08 (7.83%) answers in dissatisfied category and 06 (5.89%) answers in strongly dissatisfied category. It is evident that the corresponding falls in the category of strongly satisfied and satisfied 61.77%, which is comparatively greater than remaining categories. Furthermore, it is also submitted that the frequency of such outcome decreases vertically indicating that the scale is adjusted for convince, otherwise it can be integrated to 70% to 80%, it means that overall sample size is ranging strongly valid the result. Discussion: Nurses are not fully satisfied with their work. When the workload of Nurses increase then the level of Job satisfaction decreases because both are against each other.